Effects of rapeseed meal fiber content on phosphorus and calcium digestibility in growing pigs fed diets without or with microbial phytase. (29th June 2017) - Bournazel, M.; Lessire, M.; Duclos, M. J.; Magnin, M.; Même, N.; Peyronnet, C.; Recoules, E.; Quinsac, A.; Labussière, E.; Narcy, A.
Abstract : The optimization of dietary phosphorus (P) and calcium (Ca) supply requires a better understanding of the effect of dietary fiber content of co-products on the digestive utilization of minerals. This study was designed to evaluate the effects of dietary fiber content from 00-rapeseed meal (RSM) on P and Ca digestibility throughout the gastrointestinal tract in growing pigs fed diets without or with microbial phytase. In total, 48 castrated male pigs (initial BW=36.1±0.4 kg) were housed in metabolic crates for 29 days. After an 8-day adaptation period, pigs were allocated to one of the eight treatments. The impact of dietary fiber was modulated by adding whole RSM (wRSM), dehulled RSM (dRSM) or dRSM supplemented with 4.5% or 9.0% rapeseed hulls (dRSMh1 and dRSMh2). Diets contained 0 or 500 phytase unit of microbial phytase per kg. From day 14 to day 23, feces and urine were collected separately to determine apparent total tract digestibility (ATTD) and apparent retention (AR) of P and Ca. At the end of the experiment, femurs and digestive contents were sampled. No effect of variables of interest was observed on growth performance. Microbial phytase increased ATTD and AR of P ( P <0.001) but the P equivalency with the wRSM diet was lower than expected. Moreover, stomach inorganic P ( i P) solubility was improved by microbial phytase ( P <0.001). The ATTD of Ca was not affected by microbial phytase which increased AR of Ca and femur characteristics ( P <0.05). Ileal recovery of P was not affected by microbial phytase but cecal recovery was considerably reduced by microbial phytase ( P <0.001). The decrease in digesta pH between the distal ileum and cecum (7.6 v . 5.9) enhanced the solubility of i P and may have improved its absorption, as supported by the negative relationship between soluble i P and pH ( R 2 =0.40, P <0.001 without microbial phytase and R 2 =0.24, P =0.026 with microbial phytase). The inclusion of hulls improved the solubility of i P ( P <0.05). In conclusion, dehulling does not largely increase nutrient digestibility although dRSM seems to improve the efficacy of microbial phytase in releasing phosphate in the stomach. Moreover, dietary fiber may affect solubilization process in the cecum which potentiates the effect of microbial phytase on P digestibility.